Application of Blockchain Technology in Smart Contracts: A Systematic Literature Review - Fauziah, Zaleha; Latifah, Haznah; Omar, Xavier; Khoirunisa, Alfiah; Millah, Shofiyul (Pandawan, 2020)
Associated with the current development of the emergence of many technologies that have increased in the world, especially in industry, one of which is the blockchain which is a new technology that is undergoing drastic density, this technology has data that is difficult to manipulate so that the blockchain has data security very trusted, and every record of all the contents of the transaction data can be known from one server to another server so that both parties know each other what the activities are carried out. The recording of transactions in this blockchain technology is connected in one block that is secured directly by a computer network, the blockchain itself has several applications such as Cryptocurrency or can also be called digital currencies, and Smart Contracts. This Smart Contracts is an application owned by blockchain technology that carries out an agreement or digital agreement in the computer program code that is entrusted by both parties stored in the blockchain database, so that it cannot be changed by anyone or the help of other parties, then no longer needed entities that can be trusted in using Smart Contracts. These Smart Contracts help to process the exchange of money, shares and property. Currently there are many industries that use Smart Contracts, such as the business industry that records financial services, the health industry which records data on patient health history, even the insurance and government industries also use Smart Contracts, therefore the existence of Smart Contracts is useful to avoid an intermediary service so that a transaction process will be trtransparent.